Metabolomic profiling of bovine leucocytes transformed by Theileria annulata under BW720c treatment - Hong-xi Zhao; Xia Li; Jun-long Liu; Gui-quan Guan; Xin-gang Dan (Parasites & Vectors, 2022)
Abstract Background When Theileria annulata infects host cells, it undertakes unlimited proliferation as tumor cells. Although the transformed cells will recover their limited reproductive characteristics and enter the apoptosis process after treatment with buparvaquone (BW720c), the metabolites and metabolic pathways involved are not clear. Methods The transformed cells of T. annulata were used as experimental materials, and the buparvaquone treatment group and DMSO control group were used. Qualitative and quantitative analysis was undertaken of 36 cell samples based on the LC–QTOF platform in positive and negative ion modes. The metabolites of the cell samples after 72 h of drug treatment were analyzed, as were the different metabolites and metabolic pathways involved in the BW720c treatment. Finally, the differential metabolites and metabolic pathways in the transformed cells were found. Results A total of 1425 metabolites were detected in the negative ion mode and 1298 metabolites were detected in the positive ion mode. After drug treatment for 24 h, 48 h, and 72 h, there were 56, 162, and 243 differential metabolites in negative ion mode, and 35, 121, and 177 differential metabolites in positive ion mode, respectively. These differential metabolites are mainly concentrated on various essential amino acids. Conclusion BW720c treatment induces metabolic disturbances in T. annulata-infected cells by regulating the metabolism of leucine, arginine, and l-carnitine, and induces host cell apoptosis. Graphical abstract